The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/dc.24696
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of p16 immunocytochemistry in metastatic cervical lymph nodes in head and neck cancers

Abstract: Background Human papilloma virus (HPV) testing can be useful in work‐up of patients presenting with cervical node metastasis, suspected to be of head and neck origin as HPV positive tumors show better response to therapy. The current study was planned to detect HPV in aspirates from metastatic cervical nodes using p16 immunocytochemistry in head and neck squamous cell carcinoma (HNSCC). Further correlation of HPV status between node metastasis and primary tumor was done. Methods The prospective study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…11 Reports of various testing options on FNA samples have included p16 IHC, DNA ISH, the Cobas HPV test, the Cervista HR-HPV and Cervista HPV16/HPV18 assays, and the Hybrid Capture 2 assay. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][29][30][31][32] With regard to performing p16 ICC on Cancer Cytopathology May 2022 cytology samples, the CAP guidelines recommend individual laboratories validate the appropriate cutoff for a positive result. This allows laboratories the flexibility to use their preferred cytology sample on which to perform p16 staining.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 Reports of various testing options on FNA samples have included p16 IHC, DNA ISH, the Cobas HPV test, the Cervista HR-HPV and Cervista HPV16/HPV18 assays, and the Hybrid Capture 2 assay. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][29][30][31][32] With regard to performing p16 ICC on Cancer Cytopathology May 2022 cytology samples, the CAP guidelines recommend individual laboratories validate the appropriate cutoff for a positive result. This allows laboratories the flexibility to use their preferred cytology sample on which to perform p16 staining.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The study by Kapoor et al used a 50% ICC staining cutoff and found that sensitivity and specificity for the detection of HPV in cervical lymph node metastasis in head and neck SCC were 82.4% and 100%, respectively. 26 Yang et al performed p16 ICC on 50 neck-mass FNAs diagnosed as SCC compared with corresponding surgical tissue and used receiver operator curve analysis, which demonstrated that the best cutoff was 50% staining on smears with 74% sensitivity and 100% specificity. 25 In our study, we used FFPE surgical tissue for comparison p16 IHC staining and found an overall concordance rate of 87.5%.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations